A divulgação científica e a temática vacina: uma análise na revista Superinteressante (1988-2021) - Cavalli, Mariana Bolake (2022)
The present research work was developed based on the disclosure that Superinteressante magazine makes about scientific questions to its readers, composed mostly by the lay population to scientific methods. One of these questions that has a meaningful impact on social life and will be analyzed in this work is the vaccine thematic. The objective of this research was to understand which way the Superinteressante magazine approaches this thematic to its audience referring to the theme, in the year 1988 until August 2021, when the data for this research were constructed. For this, all the articles of the magazine were selected by digital and physical means, in the time period identified above, which have the word “vaccine” in their tittle contemplating a corpus of 95 texts. From the analyzed reports, it was possible to elaborate a classification containing 10 dispositions. The analysis of the texts of the Superinteressante magazine editions allowed identifying a greater production of articles with the theme of vaccines, from the year 2015, paying attention to the growing debate about vaccine hesitation in this period, which reached high levels, especially in the year of 2020, with the onset of the Covid-19 pandemic. From the corpus of 95 texts, 20 were selected for an analysis of the discursive resources present in them, observing the didactic elements (metaphor, analogy, naming and exemplification), the attractiveness elements (cold hook, toil, sensationalism and innovation) and credibility elements (scientist's voice, presentation of data and processes). It was noticed that the most used didactic elements are the comparisons, which bring examples to bring the reader closer to the addressed content. The attractiveness elements have the function of capturing the reader's attention, so that he becomes interested in the topic. Credibility elements are used as a way of guaranteeing the veracity of the content, justifying it using data or people from the subject area in the Scientific Dissemination text. These resources and elements that appear in the texts of Scientific Dissemination have the function of facilitating the reader's understanding of the subjects disclosed. Such texts can be a source of information to different audiences, including students. In this sense, when considering Science Teaching, the analyzed texts can be used in the classroom, in the understanding of its characteristics, limits and possibilities.